Home Filing System (HOFIS) / Nura Lina Md Elias … [et al.] - Md Elias, Nura Lina; Hashim, Maryam Jameelah; Ariffin, Nur Afizah; Osman, Idris (Division of Research and Industry Linkages, 2017)
Home Filing System (HoFiS) is a record management tool designed to meet a household filing system. It comprises of both financial filing system (FinS) and personal filing system (PinS) that will be safe keep in a designated cabinet. The system enables family institutions to stay organized at all time. The objectives include facilitating proper safekeeping of households’ personal records and financial documents, to create awareness about personal finance record management system and to ensure households’ financial and personal documents being monitored periodically. FinS composes of seven (7) areas of personal financial planning namely personal financial planning, tax planning, consumer credit, risk management, investment planning, retirement planning and estate planning. Since Personal Financial Planning course (FIN533) being offered as common subject, FinS is designed as teaching tools that will assist teaching and learning process in the classroom. The lecturers will demonstrate and articulate this system throughout the syllabus. At the end of the course, the students are expected to develop or create their own filing system. In addition, PinS is designed for records and safekeeping of a household’s personal documents such as identification documents, medical records, certificates, and house appliances maintenance records. Both FinS and PinS wilt be safe keep in a designated cabinet. This product is the first in its kind that provides competitive advantage in financial product innovation. Despite it usefulness and commercial value, there is yet a similar product that offers record management system for a household either in the domestic or worldwide market